A Review of Triterpenoids and Their Pharmacological Activities from Genus Kadsura - Yong-Bei LIU; Yu-Pei YANG; Han-Wen YUAN; Ming-Jiao LI; Yi-Xing QIU; Muhammad Iqbal CHOUDHARY; Wei WANG (KeAi Communications Co., Ltd., 2018)
ABSTRACT: Plants in genus Kadsura, belong to the Schisandraceae family including genus Schisandra and genus Kadsura, revealed folk efficacy and medicinal application in the treatment of rheumatoid arthritis and gastroenteric disorders for a long history. Previous study indicated that plants from genus Kadsura mainly contain lignans, triterpenoids and essential oils, and showed the active compounds were lignans and triterpenoids. Among all compounds from Schisandraceae family, the triterpenoids between the genus Schisandra and genus Kadsura had obvious differences. In this paper, we reviewed 214 triterpenoids and their pharmacological activities reported from genus Kadsura in the past 30 years (from 1987 to 2017), aiming to provide reference for further study. Keywords: Kadsura, Triterpenoids, Structures, Classifications, Pharmacological activities